Pengembangan Kawasan Agropolitan untuk Pemberdayaan Masyarakat Lokal (Studi pada Kawasan Usaha Kecil dan Menengah Kecamatan Bumiaji Kota Batu) - Angga Putra Utama (Jurnal Administrasi Publik, 2014)
Abstract: Agropolitan Region Development for The Empowerment of Local Community (Study at The Region of Small and Medium Enterprises in Bumiaji Subdistrict, Batu City) Bumiaji Subdistrict of Batu City is a quite possible and strategic to be developed as agropolitan region because this Subdistrict contains various agricultural products, including fruits and vegetables, which mark the distinctive feature of Batu City. Farmland in Bumiaji Subdistrict is still preserved. Community economic is therefore improved by developing small and medium enterprises based on agriculture. This research use descriptive a qualitative approach to collect the data needed from BAPPEDA and DISKOPERINDAG, The community around the area and interviewing as many as 2 agropolitan UKM group representing 32 people and 2 people from the office of its members. This research result indicates Batu City made a group of work agropolitan (POKJA ) through BAPPEDA to do the work plan agropolitan area development. While DISKOPERINDAG Batu City very play an active role in providing training to the farmers in the area of agropolitan to develop agricultural products. Keywords: Empowerment, Region Development, Government Role Abstrak: Pengembangan kawasan Agropolitan untuk Pemberdayaan Masyarakat Lokal (Studi pada Kawasan Usaha Kecil dan Menengah Kecamatan Bumiaji Kota Batu). Kota Batu di Kecamatan Bumiaji merupakan salah satu kawasan strategis yang sangat tepat untuk pengembangan kawasan agropolitan, karena terdapat beberapa hasil pertanian yang menjadi ciri khas dari Kota batu seperti buah dan sayuran. Maka perlu pengembangan ekonomi masyarakat melalui pemberdayaan usaha kecil dan menengah dengan program pengembangan kawasan agropolitan. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan mengumpulkan data yang dibutuhkan dari BAPPEDA dan DISKOPERINDAG, serta mewawancarai masyarakat di sekitar kawasan agropolitan sebanyak 2 kelompok UKM yang mewakili 32 orang anggotanya dan dari dinas 2 orang. Hasil penelitian ini menunjukkan Kota Batu membuat kelompok kerja agropolitan (POKJA) melalui BAPPEDA untuk melakukan rencana kerja pengembangan kawasan agropolitan. sedangkan DISKOPERINDAG Kota Batu sangat berperan aktif dalam memberikan pelatihan kepada masyarakat petani di kawasan agropolitan untuk mengembangkan produk hasil pertanian. Kata kunci: Pemberdayaan, Pengembangan Kawasan, Peran Pemerintah Â